2022
DOI: 10.1353/hub.2021.0010
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Scale Genetic Profile and Admixture History of Two Hmong-Mien–Speaking Miao Tribes from Southwest China Inferred from Genome-wide Data

Abstract: As the dominant indigenous minority in southern China, Hmong-Mien-speaking Miao people were thought to be the descendants of Neolithic Yangtze rice farmers. However, the fine-scale population structure and genetic profile of the Miao populations remain unclear due to the limited Miao samples from southern China and Southeast Asia. We genotyped 19 individuals from the two largest Miao tribes in Guizhou Province (Southwest China) via SNP chips and co-analyzed the data with published modern and ancient East Asian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…In the autosomal study, the HM population was found to carry a specific genetic component [ 5 , 6 ] and receive gene flow from the ancestors of southern East Asians [ 7 ] and Sino–Tibetan-related ancestry [ 6 ]. However, including some other recent studies [ 8 11 ], genetic research in the HM population is mainly based on sparse single-nucleotide polymorphisms (SNPs), with the Miao population as the main population and the lack of Yao population data. Limited by data, the demographic history model and adaptive evolution of the HM populations are still not comprehensive and clear.…”
Section: Introductionmentioning
confidence: 99%
“…In the autosomal study, the HM population was found to carry a specific genetic component [ 5 , 6 ] and receive gene flow from the ancestors of southern East Asians [ 7 ] and Sino–Tibetan-related ancestry [ 6 ]. However, including some other recent studies [ 8 11 ], genetic research in the HM population is mainly based on sparse single-nucleotide polymorphisms (SNPs), with the Miao population as the main population and the lack of Yao population data. Limited by data, the demographic history model and adaptive evolution of the HM populations are still not comprehensive and clear.…”
Section: Introductionmentioning
confidence: 99%